2013
DOI: 10.1016/j.jvs.2013.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes following endovascular repair of abdominal aortic aneurysms based on size threshold

Abstract: EVAR for small AAAs shows improved long-term outcomes than for age-matched patients with larger aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…Similar to prior reports, we found no difference between patient survival and freedom from any intervention between the two groups 4,10,11,12 . Significant differences were noted between Groups for Aortic Neck diameter (p =0.0179), Aortic neck length (p= 0.0016), Aortic neck angle (p = 0.0101) and Aneurysm angle (p =0.0045) measurements.…”
Section: Resultssupporting
confidence: 90%
“…Similar to prior reports, we found no difference between patient survival and freedom from any intervention between the two groups 4,10,11,12 . Significant differences were noted between Groups for Aortic Neck diameter (p =0.0179), Aortic neck length (p= 0.0016), Aortic neck angle (p = 0.0101) and Aneurysm angle (p =0.0045) measurements.…”
Section: Resultssupporting
confidence: 90%
“…These results are similar to those we reported earlier 3,4 or those published of the National Inpatient Sample database 2 or reported by others. 11,28,[32][33][34] The low overall early mortality was likely the reason we did not find differences in our subgroups. Factors associated with early mortality in our study included only advanced age and high surgical risk, similar to factors observed in earlier studies.…”
Section: Discussionmentioning
confidence: 74%
“…[12][13][14][15] The most serious consequence of type III endoleaks is repeat exposure of the aneurysm sac to direct arterial blood pressure with subsequent aneurysm sac enlargement and death from AAA rupture. Additionally, it has now been recognized that endograft uncoupling can obstruct aortic blood flow resulting in AAA thrombosis and lower extremity ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The 2.4% incidence of type IIIa endoleaks reported here is comparable to that of recent studies using Endologix and other modular endografts, which found a 2% to 2.7% long-term incidence of type III endoleaks across multiple endograft platforms. 14,17 In a recent detailed analysis of 108 patients treated with Endologix AFX endograft, Welborn et al 18 reported a 2.3% incidence of type IIIa endoleaks. In addition, independent core laboratory data extracted from two recently presented, but as yet unpublished studies, of the Endologix AFX system by Motaganahalli et al and Arthurs et al found four type IIIa endoleaks in 127 combined patients (3.1%) monitored an average of 10 months after elective EVAR.…”
Section: Discussionmentioning
confidence: 99%